The effect of i-deals on employees’ unethical behavior during the COVID-19 pandemic: The roles of hubristic pride and grandiose narcissism - Liu, Zhihao; Zhang, Xiaoyan; Xu, Hanzhi; Deng, Hui; Li, Jiajia; Lan, Yuanyuan (Frontiers in Psychology, 2022)
The COVID-19 pandemic has created enormous challenges for organizations and employees. Due to the effectiveness of idiosyncratic deals (i-deals for short) in management practices, more and more organizations use this human resource management tool to address the challenges posed by the COVID-19 pandemic. However, whether there are potential risks or negative effects of i-deals in the COVID-19 pandemic environment is not very clear. Drawing upon social cognitive theory, we proposed that i-deals may foment focal employees’ unethical behavior by triggering their hubristic pride, and such process may be moderated by their trait of grandiose narcissism. We conducted a survey during the COVID-19 outbreak and tested our hypotheses with 492 samples from Shandong Province, China. Consistent with predictions, we found a positive relationship between i-deals and hubristic pride, which, in turn, increased their unethical behavior. And the relationship between i-deals and unethical behavior was mediated by hubristic pride. Furthermore, grandiose narcissism strengthened the positive relationship between i-deals and hubristic pride, as well as the indirect effect of i-deals on unethical behavior via hubristic pride. Our findings contributed to the literature on i-deals and provided guidance for organizations to address the challenges posed by the COVID-19 pandemic..